2008
DOI: 10.1111/j.1530-0277.2008.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Access to 20% Ethanol Induces High Ethanol Consumption in Long–Evans and Wistar Rats

Abstract: Background There has been some difficulty getting standard laboratory rats to voluntarily consume large amounts of ethanol without the use of initiation procedures. It has previously been shown that standard laboratory rats will voluntarily consume high levels of ethanol if given intermittent-access to 20% ethanol in a 2-bottle-choice setting [Wise, Psychopharmacologia 29 (1973), 203]. In this study, we have further characterized this drinking model. Methods Ethanol-naïve Long–Evans rats were given intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

65
636
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(712 citation statements)
references
References 21 publications
65
636
11
Order By: Relevance
“…All mice were group‐housed and maintained at a 12/12 hour light/dark cycle. Adult post pubertal age‐matched male Rcc Han Wistar rats (Harlan, Horst, Netherlands) were used as they are known to voluntarily consume alcohol using the intermittent access model and thereby reach physiological relevant blood alcohol concentrations (Simms et al., 2008). They were housed individually in high Macrolon III cages covered with filter tops (Tecniplast, Varese, Italy) and maintained on a 12‐hour reversed light dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…All mice were group‐housed and maintained at a 12/12 hour light/dark cycle. Adult post pubertal age‐matched male Rcc Han Wistar rats (Harlan, Horst, Netherlands) were used as they are known to voluntarily consume alcohol using the intermittent access model and thereby reach physiological relevant blood alcohol concentrations (Simms et al., 2008). They were housed individually in high Macrolon III cages covered with filter tops (Tecniplast, Varese, Italy) and maintained on a 12‐hour reversed light dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Fluid intake was measured 30 min after the bottle exchange on each ethanol drinking day. The intermittent drinking paradigm has previously been shown to produce relatively high levels of ethanol intake in male Long-Evans rats (Wise, 1973;Simms et al, 2008). Furthermore, this drinking paradigm has been shown to engender elevated ethanol intake in SI compared with GH rats (Chappell et al, 2013;Skelly et al, 2015).…”
Section: Ethanol Drinking Proceduresmentioning
confidence: 99%
“…We also showed that chlorzoxazone, an FDA-approved SK activator used for decades as a centrally acting myorelaxant, significantly reduces excessive alcohol intake in rats with intermittent access to ethanol, but does not reduce the more moderate alcohol intake in rats with continuous access to alcohol (Hopf et al, 2011). Alcohol intake in intermittent-access rats shows a number of other features, which have been considered to perhaps model some aspects of human alcoholism, including escalation of intake, sensitivity to compounds that reduce alcohol intake in human alcoholics (Steensland et al, 2007; Novel therapeutic strategies for addiction G Addolorato et al ............................................................................................................................................................... Simms et al, 2008;McKee et al, 2009) and aversion-resistant and perhaps compulsive alcohol intake (Hopf et al, 2010b). Thus, the SK activator chlorzoxazone may represent a potent and immediately accessible treatment for human alcoholism.…”
Section: Sk-type Calcium-activated Potassium Channelsmentioning
confidence: 99%